Linguagem e performatividade na formação inicial de professores de língua inglesa - Rocha, Daniella Corcioli Azevedo (2019)
This research is inserted in the field of studies related to teacher formation and was developed based on the premise that, as the pre-service formation of English language teachers (LI) occurs not only in language, but also by language, it is necessary to look at this process taking into account the performative character of speech acts present in this context (AUSTIN, 1990). Thus, its main objective was to investigate how the theoretical studies, the teacher's teachings about these theoretical studies and the discussions undertaken during the investigation period were re-signified by the future teachers of the pre-service formation course investigated. It was also my goal to investigate how the participants of this study re-signified the different methods and approaches to teaching, and how these re-significations emerged in their practices during the micro-classes planned and taught by them during the English Language Teaching Methodology (MLI) classes. With these goals in mind, I sought theoretical support in the studies encompassed by Pragmatics and Applied Linguistics (LA). The field of pragmatics helped me to discuss language issues as an action and not just as a way of expressing or describing things in the world (AUSTIN, 1990; OTTONI, 2002; PINTO, 2012; RAJAGOPALAN, 2010 e 2014). The concepts of Speech Acts and apprehension were crucial to this study. LA helped me discuss teacher education and also the issues surrounding subject and subjectivity in relation to the practices developed in the processes of teacher education (CORACINI E BERTOLDO, 2003; KUMARAVADIVELU, 2001; MOITA LOPES, 2006). In a broader perspective, this research found methodological support in the qualitative interpretative approach (CHIZZOTI, 2003, CELANI, 2005). For the development of this study, eight MLI classes were audio-recorded, and later transcribed. The corpus was also composed of questionnaires answered by the student-teachers in their pre-service formation, all participants in the research; a semi-structured interview, answered by the class teacher; field notes taken by the researcher; lesson plans of the micro-classes prepared by the participant student teachers; and the course plan of the taught subject during the teaching of which this study took place. In regards to the main and most striking re-significations of the research participants, I would like to highlight the fact that they took the pre-service formation as being responsible for providing everything they might need after graduation, when they will be exercising their professions. Another very important aspect regarding the results found from this investigation is related to the fact that the participants' previous experiences constituted the subjective and contextual influences that most determined the resignifications of the study participants. Nevertheless, they have never failed to recognize the value and importance of the initial training course they were taking.